From the historiography of the school space to the history of the school place - Chahin, Samira Bueno (Pro-posições, 2024)
Abstract By taking the educational dimension of the school space as true, the article starts from the emergence of the open plan as a design solution for school spaces to achieve recognition of everyday pedagogical practices as active producers of essential spatialities for the interpretation of the school-place. Thus, the relevance of also mobilizing the marks left by the unpredictability of everyday uses on the school-building as a regime of historical interpretation of the school space is perceived. Through a bibliographical incursion and mobilizing the idea of unpredictability as an interpretative key, a historiographical gap is identified in the general absence of attentive approaches to the impacts of daily adaptations made on school building. Resumo Ao tomar a dimensão educativa do espaço escolar como verdadeira, o artigo parte da emergência da planta livre como solução projetual de espaços escolares para alcançar o reconhecimento das práticas pedagógicas cotidianas como produtoras ativas de espacialidades essenciais para a interpretação do lugar-escola. Percebe-se assim a relevância de mobilizar também as marcas deixadas pela imprevisibilidade dos usos cotidianos sobre o edifício-escola como regime de interpretação histórica do espaço escolar. Por meio de uma incursão bibliográfica e mobilizando a ideia de imprevisibilidade como chave interpretativa, identifica-se uma lacuna historiográfica na ausência generalizada de abordagens atentas aos impactos de adaptações cotidianas feitas sobre a edificação escolar.